Supporting Human-Automation Interaction in the Rail Industry by Applying Lessons from Aviation. (September 2015) - Sebok, Angelia; Wickens, Christopher; Laux, Lila; Jones, Michael
This paper describes a project to identify lessons learned from human automation interaction and the aviation industry and apply them to the rail industry. Specifically, the project addresses positive train control (PTC) automation in the locomotive cab. The aviation industry has decades of experience implementing automation on the flight deck. In particular, the flight management system (FMS) has offered numerous challenges and provided many lessons learned that can be applied to the rail industry. Experiences with the FMS indicate that mode complexity and mode transitions are particularly challenging. The current PTC designs have only two modes of operation, thus bypassing many of the FMS challenges. However, the possibility of mode confusion exists. This can occur if the engineer believes that PTC is active, when in fact it is not. Mixed equipage on rail lines, where some – but not all – segments of track are instrumented with PTC equipment, make this mode confusion a relevant concern.